Cardiac Remodeling: New Insights in Physiological and Pathological Adaptations - Leonardo Roever (Frontiers Research Topics, 2017)
The effective management of Cardiac remodeling(CR), remains a major challenge. Heart failure remains the leading cause of death in industrialized countries. Yet, despite the enormity of the problem, effective therapeutic interventions remain elusive. In fact, several initially promising agents were found to decrease mortality in patients recovering from myocardial infarction. Cardiac remodeling is defined as molecular and interstitial changes, manifested clinically by changes in size, mass , geometry and function of the heart in response to certain aggression. Initially, ventricular remodeling aims to maintain stable cardiac function in situations of aggression.